Antihyperglycemic and antioxidative potentials of Malaysian banana (Musa sp.) flower extracts - Tan, Shih Jen (2015)
Banana (Musa sp.) is one of the important agricultural products in Malaysia. Its flower commonly referring as ‘banana heart’ is a blossom which is usually red or dark red in color attached at the end of the bunch of banana fruits. Banana flower consumption is popular among the countries of Southeast Asia such as Malaysia, Philippines, Indonesia, and Si Lanka. In Malaysia, banana flowers are served as vegetables in preparing different types of cuisines. Previously, several studies were conducted to analyze the antioxidant capacity of different part of banana such as pulp, peel, leaves, pseudostem and flower. However, the antioxidant and antihyperglycemic properties of the Malaysian banana flowers have not been reported previously. In this study, six different cultivars of banana flower (Abu, Berangan, Nipah, Susu, Mas and Rastali) were investigated. The objectives of this study were to evaluate the antihyperglycemic and antioxidant properties of the Malaysian banana flowers. The potential of banana flowers as a dietary antihyperglyceamic agent was studied through screening of their anti-amylase and anti-glucosidase activity (%) at the concentration of 200.0 μg / ml. Overall, the anti-amylase and anti-glucosidase activity of the Malaysian banana flowers was found in the range of 47.31 - 62.58 % and 74.98 - 91.62 %, respectively. All banana flower extracts inhibited the activity of α-glucosidase better than α-amylase at the same concentration. The total phenolic and flavonoid contents were evaluated through Folin-Ciocalteu colorimetric method and aluminium chloride method, respectively. The reducing power of the banana flower was determined by ferric reducing antioxidant power (FRAP) assay. The antioxidant capacity of the banana flower was measured through the scavenging activities of the ABTS+ and DPPH radical. The Susu cultivar with the highest amount of phenolic compounds (80.13 ± 4.64 mg of Gallic acid equivalent / g of extract) was found to possess the highest and DPPH radical scavenging activity (24.73 ± 0.04 and 25.10 ± 0.15 μmole of Trolox equivalent [TE] / g of extract). This study concluded that the Malaysian banana flower was a potential postprandial hyperglycemia regulator and a good natural source of antioxidant.